Physiological and social consequences of gastrointestinal nematode infection in a nonhuman primate. (18th December 2018) - Müller-Klein, Nadine; Heistermann, Michael; Strube, Christina; Morbach, Zina M; Lilie, Navina; Franz, Mathias; Schülke, Oliver; Ostner, Julia
Abstract: Gastrointestinal nematodes are intensely studied models for host–pathogen interactions in wildlife, yet consequences of infections are not fully understood. Among the potential costs of nematode infection are physiological changes caused by immune system activation, reduction or reallocation of available energy, as well as potential social consequences in terms of decreased social activity or avoidance of infected individuals. We used experimental anthelmintic treatment to investigate effects of strongyle nematode infection in Barbary macaques ( Macaca sylvanus ), comparing 56 treated to 17 untreated individuals. Deworming success was monitored by coproscopy and infection probability estimated from patch occupancy models. Increasing strongyle infection probabilities were associated with increased fecal glucocorticoid metabolite levels and slightly decreased activity and had no significant effect on energy balance quantified as urinary C-Peptide levels. The frequency to approach into close spatial proximity of a partner was predicted by the partner's, but not focal individual's infection status, with a tendency toward infected individuals being approached less frequently. Although effects were weak, they suggest a co-occurrence of sickness behavior and avoidance of infected conspecifics, both possibly shaping social interaction patterns with potential consequences for an individual's social relationships. This study adds to the growing body of research on the complex interactions of sociality, health, and fitness in a group living species. Abstract : Barbary macaques infected with gastrointestinal parasites show signs of sickness and are avoided by conspecifics. Using experimental antiparasitic treatment, we found that strongyle nematode infections correspond to increased fecal glucocorticoid levels and slightly decreased activity in semi free-ranging macaques. Both effects are common responses to infections, implying that strongyle nematode infections cause sickness behavior. Infected individuals also tend to be avoided by conspecifics, so infections seem to have not only physiological but also social consequences.